2006
DOI: 10.2204/iodp.sd.2.02.2006
|View full text |Cite
|
Sign up to set email alerts
|

IODP Expedition 307 Drills Cold-Water Coral Mound Along the Irish Continental Margin

Abstract: Introduction Over the past decade, oceanographic and geophysical surveys along the slope of the Porcupine Seabight off the southwestern continental margin of Ireland have identified upwards of a thousand enigmatic mound-like structures (Figs. 1 and 2). The mounds of the Porcupine Seabight rise from the seafl oor in water depths of 600–900 m and formimpressive conical bodies several kilometers wide and up to 200 m high. Although a few mounds such as Thérèse Mound and Galway Mound are covered by a thriving thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(35 citation statements)
references
References 7 publications
2
33
0
Order By: Relevance
“…In general, the biomarker data show lower abundance of past microbial communities in the mound section compared to the sediments below the mound base and from the reference site. Biomarkers for living microbial populations were not detected in the mound sequence, which is in coherence with relatively low cell count data (Ferdelman et al, 2006). Methane, ethane and propane were detected below the mound.…”
Section: Of Microbes and Moundssupporting
confidence: 75%
See 1 more Smart Citation
“…In general, the biomarker data show lower abundance of past microbial communities in the mound section compared to the sediments below the mound base and from the reference site. Biomarkers for living microbial populations were not detected in the mound sequence, which is in coherence with relatively low cell count data (Ferdelman et al, 2006). Methane, ethane and propane were detected below the mound.…”
Section: Of Microbes and Moundssupporting
confidence: 75%
“…Meanwhile, IODP Expedition 307 on Challenger Mound in Porcupine Seabight off Ireland had drilled and sampled in detail a full mound section (Ferdelman et al, 2006;Kano et al, 2007;Foubert and Henriet, 2009), IOC-UNESCO had launched the Geosphere-Biosphere Coupling processes (GBCP) programme with a focus on capacity building around mound research, mound scientists had teamed up in projects like CARBONATE (ESF EuroMARC -Carbonate mound drilling at mid-latitudes) and with microbiologists in MiCROSYSTEMS (ESF EuroDIVERSITY -Microbial Diversity and Functionality in Cold-water Coral Ecosystems) and microbialites were found to form a substantial component… of sub-recent tropical reefs (IODP Tahiti Exp. 310, ESF EuroMARC project CHECREEF)!…”
Section: Introduction: Carbonate Mounds In Shallow and Deep Timementioning
confidence: 99%
“…The Challenger Mound (781–815 m water depth) is a prominent mound structure, 155 m in height and partially buried with sediment and dead cold-water coral ( Lophelia pertusa ) rubble (Ferdelman et al ., 2006). It is one of 66 mounds which make up the Belgica Mound Province in the Porcupine Seabight on the south-west Irish continental margin (Ferdelman et al ., 2006; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Seismic profiles have shown that some mounds are covered by tens of metres of sediment or dead coral rubble (De Mol et al ., 2002; Huvenne et al ., 2007) and others are slowly being buried (e.g. Challenger Mound, Ferdelman et al ., 2006). There are also living mounds with a thriving community of cold-water corals ( Lophelia pertusa and Madrepora oculata ) in close association with other organisms as part of a diverse cold-water coral reef ecosystem (De Mol et al ., 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation